2017
DOI: 10.3389/fneur.2017.00081
|View full text |Cite
|
Sign up to set email alerts
|

Refixation Saccades with Normal Gain Values: A Diagnostic Problem in the Video Head Impulse Test: A Case Report

Abstract: Refixation saccades with normal gain value occur more frequently with increasing age. The phenomenon has also been observed in different vestibular disorders. In this case, we present a young male with normal gain value and refixation saccades tested with the video head impulse test (vHIT) the day after his cochlear implantation. One month after surgery, refixation saccades were no longer present. This suggests that refixation saccades can occur as a result of temporary pathology such as surgery. Refixation sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
(9 reference statements)
0
18
0
1
Order By: Relevance
“…cHIT is able to detect the overt saccades, while the covert saccades remain unnoticeable 25,26. We did not consider isolated presence of saccades but the low gain, since saccades frequency may increase with age even with normal gain 27,28.…”
Section: Discussionmentioning
confidence: 99%
“…cHIT is able to detect the overt saccades, while the covert saccades remain unnoticeable 25,26. We did not consider isolated presence of saccades but the low gain, since saccades frequency may increase with age even with normal gain 27,28.…”
Section: Discussionmentioning
confidence: 99%
“…For the vHIT, an abnormal result was denoted by lower than normal vestibulo-ocular reflex gain (VOR) in the semicircular canals with catch up overt and covert saccades and by normal VOR gain with replicable and repeatable overt and covert saccades. Normal VOR gain with catch up refixation saccades after vestibular pathology have been recently identified as an important observation in the evolving literature with the vHIT (18). A minimum of 10 thrusts in different semicircular canals (laterals and right anterior left posterior RALP and left anterior right posterior LARP) were achieved to draw meaningful conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…The role of saccades in interpreting the vHIT has gathered momentum (79) and we have explained the importance of saccades in the presence of normal VOR gain in our Methods section (36,37). In the current series, they were deemed pathological in about a half of the cohort localizing accurately to the side of the third window defect.…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies ( 33 , 34 ) indicate that vertical canal gains are lower in the pediatric population than in adults similar to what we have also found using similar equipment in children with normal vestibular function ( 35 ). Saccades, rather than VOR gain, were deemed as pathological weakness as studies have shown that saccades can occur with normal VOR gain in vestibular hypofunction ( 36 , 37 ). Two senior clinicians (SDG and SR) analyzed the saccades in the current series independently.…”
Section: Methodsmentioning
confidence: 99%